Existence and Convergence Theorems of Best Proximity Points - Moosa Gabeleh; Naseer Shahzad (Journal of Applied Mathematics)
The aim of this paper is to prove some best proximity point theorems for new classes of cyclic mappings, called pointwise cyclic orbital contractions and asymptotic pointwise cyclic orbital contractions. We also prove a convergence theorem of best proximity point for relatively nonexpansive mappings in uniformly convex Banach spaces.